An Interventional Study to Evaluate Knowledge, Attitude, and Practice Regarding Insulin Administration among Diabetic Patients at a Tertiary Care Hospital in Dakshina Kannada - A, Ramakrishna Shabaraya; Fernandes, Blessy; Kumari, Suchetha (Indian Journal of Pharmacy Practice)
Background: Hyperglycemia is the defining characteristic of Diabetes Mellitus (DM) caused by abnormalities in insulin secretion, insulin action or both. In order to prevent complications, optimal glycemic management is necessary to lower DM morbidity and mortality. The technique for injecting insulin is one of the areas where mistakes are most likely to occur. Good knowledge, a positive attitude and right practice of insulin self-administration leads to better outcome. Materials and Methods: An interventional study was carried out for subjects who were on insulin of either gender for a period of 6 months with a validated questionnaire to assess the knowledge, attitude and practice on insulin administration. Results: A total of 100 patients were interviewed, of which 54% were male and 46% were female. The mean knowledge score was 3.03±1.85, mean attitude score was 3.22±1.46 and the mean practice score was 3.0±1.49. On categorizing the scores, 31% were found to have good knowledge while 23% were found to have average level of knowledge and 46% had poor knowledge. Favorable, satisfactory and unfavorable attitude was found in 23%, 51% and 32% of the participants, respectively. The level of practice was found to be good in 17%, satisfactory in 42% and inadequate in 41% of subjects. Conclusion: In the study, suboptimal responses to insulin delivery were reported. Patients’ KAP was enhanced by education regarding insulin administration. Therefore, during each hospital visit, barriers should be filled by instructing patients on how to inject insulin.
Keywords: Attitude; Diabetes; Insulin administration; Knowledge; practice